2021
DOI: 10.1021/acs.chemrestox.1c00306
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Influences Methylmercury-Induced Lipid Accumulation and Mitochondrial Toxicity in Caenorhabditis elegans

Abstract: Metabolic effects of methylmercury (MeHg) are gaining wider attention. We have previously shown that MeHg causes lipid dysregulation in Caenorhabditis elegans (C. elegans), leading to altered gene expression, increased triglyceride levels and lipid storage, and altered feeding behaviors. Transcriptional regulators, such as transcription factors and microRNAs (miRNAs), have been shown to regulate lipid storage, serum triglycerides, and adipogenic gene expression in human and rodent models of metabolic diseases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…Intriguingly, miRNAs also regulate RNAi sensitivity to endogenous and exogenous siRNAs [ 61 ]. Several studies have shown that enzymes in the siRNA biogenesis might be involved in MeHg-induced toxicity in C. elegans [ 62 , 63 , 64 ].…”
Section: Mehg Mirna and Rna Interference (Rnai)mentioning
confidence: 99%
See 2 more Smart Citations
“…Intriguingly, miRNAs also regulate RNAi sensitivity to endogenous and exogenous siRNAs [ 61 ]. Several studies have shown that enzymes in the siRNA biogenesis might be involved in MeHg-induced toxicity in C. elegans [ 62 , 63 , 64 ].…”
Section: Mehg Mirna and Rna Interference (Rnai)mentioning
confidence: 99%
“…The mutant strain ( rrf-3 (pk1426)) is hypersensitive to RNAi and resistant to MeHgCl-induced toxicity [ 62 , 63 ]. Another independent study showed that C. elegans mutant strains, including ( rrf-1 (pk1417)) and ( rrf-3 (pk1426)), were also resistant to MeHgCl-induced toxicity [ 64 ]. Additionally, the molecular components in the early steps of siRNA genesis may also be involved in MeHg-induced toxicity.…”
Section: Mehg Mirna and Rna Interference (Rnai)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, lipid dysregulation could be modified by altering the ability of the worms to produce miRNAs. Worms that expressed more miRNA than wild type were protected from MeHg toxicity and lipid dysregulation, whereas worms that could not produce functional miRNA had exacerbated toxicity and lipid dysregulation in response to MeHg [19].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that miRNA expression is altered in the adipose tissue of individuals with metabolic disorders [ 241 , 242 ]. Altering the ability of C. elegans to express miRNA significantly affected the ability of MeHg to cause lipid dysregulation [ 243 ]. This suggests that MeHg may affect the expression of the miRNA sequences involved in lipid homeostasis.…”
Section: Introductionmentioning
confidence: 99%